Compatibility Test Consorcium of Thermophilic Bacteria Producing Xylanase Enzym from The Hot Water of Mudiak Sapan (MS18, MSS15, MSS11, MS16) - Irdawati; Indrawani Matondang; Linda Advinda; Azwir Anhar; Yusrizal Y (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Mudiak Sapan hot spring, South Solok Regency, West Sumatra is one of the hot springs where there are various species of thermophilic bacteria that produce xylanase enzymes. The xylanase enzyme is a group of enzymes that has the ability to hydrolyze xylan (hemicellulose) or polymers into xylose and xylo-oligosaccharides. The purpose of this study was to test the compatibility of bacterial isolates to become a xylanase-producing bacterial consortium. This research is a descriptive research that informs the compatibility of thermophilic bacterial isolates from the Mudiak Sapan hot springs. The method used in this study was disk diffusion, based on the research, it was found that 5 combinations of compatible xylanase enzyme-producing isolates were MS18 x MSS11; MS18 x MSS15; MSS18 x MS16 ; MSS11 x MS16 ; MSS15 x MS16 and 1 combination of incompatible isolates namely MSS11 x MSS15 which had an inhibition zone of 0.645 cm.